Identifying leukemia stem cells: is it feasible and does it matter? - Lutz, Christoph; Hoang, Thanh Van; Buß, Eike Christian; Ho, Anthony Dick (Cancer letters, 2013)
Present evidence indicates that acute myeloid leukemia (AML) is a stem cell disease. Leukemia stem cells (LSC) might originate from malignant transformation of normal hematopoietic stem cells (HSC), or alternatively, from progenitors in which the acquired mutations have re-installed a dysregulated self-renewal program. Since LSC, similar to their normal counterparts, divide extreme slowly, this might account for the ineffectiveness of conventional chemotherapy in inducing long-term cure. The present review will focus on the detection of LSC, their cellular and molecular biology, their genetic heterogeneity and on correlative studies that have demonstrated the clinical significance of estimating LSC burden. For long-term cure of AML, it is of importance to define LSC candidates and to understand their biology compared to normal HSC. Finally, we will discuss the perspectives of developing treatment strategies for eradication of LSC.
Published online: 20 July 2012
Gesehen am 12.06.2018